Revolution empirics: predicting the Arab Spring - Simplice A. Asongu; Jacinta C. Nwachukwu (African Governance and Development Institute (AGDI), 2014)
The paper examines whether the Arab Spring phenomenon was predictable by complete elimination in the dispersion of core demands for better governance, more jobs and stable consumer prices. A methodological innovation of the Generalized Methods of Moments is employed to assess the feasibility and timing of the revolution. The empirical evidence reveals that from a projection date of 2007, the Arab Spring was foreseeable between 2011 and 2012. The paper contributes at the same time to the empirics of predicting revolutions and the scarce literature on modeling the future of socio-economic events. Caveats and cautions are discussed.
Keywords: N17; O11; O20; O47; P52; 330; Arab Spring; Political Instability; Timing; Economic Growth